Quantitative and qualitative blood pressure clusters in patients of Truskavets' SPA and their hemodynamic accompaniment - Nataliya Kozyavkina; Nataliya Voronych-Semchenko; Yuliya Vovchyna; Walery Zukow; Igor Popovych (Kazimierz Wielki University, 2020)
Background. The influence of balneotherapy at the Truskavets' spa on the blood pressure (BP) of his patients is still not in the focus of researchers. Therefore, we initiated the project "Neuroendocrine-immune and metabolic mechanisms of the effect of balneotherapy on BP". The first swallow of the project is the analysis of a condition of BP and its hemodynamic support of profile patients of a resort. Materials and methods. Under an observations were 44 patients with chronic pyelonephritis and cholecystitis in the phase of remission. Testing was performed twice - on admission and after 7-10 days of standard balneotherapy. The main object of the study was BP (tonometer "Omron M4-I", Netherlands). Simultaneously the parameters of hemodynamics were determined (echocamera "Toshiba-140", Japan). Results. The optimal level of systolic BP (range 120÷129 mmHg) stated in 18,2% of cases only, high norm (130÷139 mmHg) in 14,8%, arterial hypertension (AH) I (140÷160 mmHg) - in 39,8%, AH II (over 160 mmHg) in 12,5%, however, in 14,8% of cases the BP was lower than 120 mmHg. In order to identify among the registered parameters of hemodynamics, those for which the BP clusters differ from each other, a discriminant analysis was performed. The program forward stepwise included in the discriminant model 13 parameters out of 17. The most informative among them: contractility index of left ventricle, heart work per minute, ejection fraction and time as well as end-systolic volume. Conclusion. Profile patients of Truskavets' spa are characterized by a wide range of blood pressure - from low norm to arterial hypertension II that correspond to the hemodynamics parameters.